PENERAPAN ATMEGA8 UNTUK MENGUKUR TEGANGAN KELUARAN SOLAR CELL MONOCRYSTELINE DAN POLYCRYSTELINE - Ridho’i, Ahmad; Andriawan, Aris Heri (JHP17 (Jurnal Hasil Penelitian), 2016)
At this writing, has conducted monitoring and analysis and polycrystelinemonocrysteline Solar cells based on energy efficiency, using experimental data(electricity output parameters) determine the output of the solar cell becomesindispensable if it would be a smart system. So that the data output of the solarcell as a reference for processing by atmega8. Results of the analysis showedthat the measurement clock determine the level of higher energy efficiency. Theoutput of the solar cell variations at 8 (am) to 5 (pm). Device atmega8 harilduty to process the output voltage sensing of the next solar cell is shown in theLCD display.Keywords: solar cell, energy, atmega8.